Deep learning-based spectrum sensing in cognitive radio - Chng, Li Shuang (Nanyang Technological University, 2023)
With the increase in demand for spectrum resources, cognitive radio is dependent heavily to efficiently managing the overwhelming radio spectrum scarcity. To ensure that the spectrum resources in cognitive radio are fully utilized, spectrum sensing is involved to identify the presence and absence of authorized primary users in the network and allow unauthorized secondary users to access when the spectrum is left idle.